Arthroscopic Hemitrapeziectomy and Suture Button Suspensionplasty in the Treatment of First Carpometacarpal Joint Eaton–Littler Stage 2–3 Arthrosis - Özçelik, İsmail Bülent; Uğurlar, Meriç; Sarı, Abdulkadir (Journal of Wrist Surgery, 2019)
Background Degenerative arthritis of the first carpometacarpal (CMC) joint is a common degenerative condition in the hand. Many different surgical procedures have been applied for years. However, in the studies there is no consensus about the superiority of one technique to another.Questions/Purposes In this study, we evaluated the results of the patients with first CMC Eaton–Littler stage 2–3 arthrosis who were operated to prevent first metacarpal joint lateral subluxation and migration with arthroscopic hemitrapeziectomy and suture button suspensionplasty.Patients and Methods Between 2011 and 2014, 21 patients (16 female, five male) were evaluated retrospectively. Mean age was 52.3 years. The preoperative and postoperative assessments were performed with visual analog scale (VAS) and disabilities of the arm, shoulder, and hand score (DASH) scores. The Kapandji's thumb opposition score was used to assess thumb range of movement. The patients were assessed after arthroscopy according to Badia classification.Results Mean follow-up period was 50.1 months. According to Badia classification, seven patients were found to be type 2 and 14 patients were type 3. The mean preoperative Kapandji's score was 7.6 and the mean postoperative Kapandji's score was 9.2. The mean VAS values were 8.2 preoperatively and 1.9 postoperatively. The mean preoperative DASH value was 23.4 and the mean postoperative DASH value was 5.5. The mean preoperative grip strength was 66.2 and the mean postoperative grip strength was 75.1. The mean preoperative pinch strength was 14.8 and the mean postoperative pinch strength was 20.2.Conclusion Arthroscopic hemitrapeziectomy and suture button suspensionplasty is a minimal invasive technique and can be performed with low morbidity in the treatment of first CMC joint Eaton–Littler stage 2–3 arthrosis. By this technique, the patients' existing instability and pain problems can be solved. Complications, such as loosening of the suture button at the first metacarpal at the postoperative period due to direct trauma to the first CMC joint, could be avoided using a new suture button.Type of Study/ Level of Evidence Therapeutic IV.
Keywords: arthroscopy; carpometacarpal; CMC; suture button